Dehydroxilation and Crystallization of Glasses: a DTA Study - Lago, Diana Carolina (2013)
Differential thermal analysis (DTA) is a technique frequently used for the study of the crystallization kinetics of glass powders during sintering. The effect of specific surface area on crystallization kinetics has been reported earlier. It has been shown that there is a shift in the DTA crystallization peaks towards lower temperatures for smaller particle size. This paper analyzes how the dehydroxilation endothermic peaks that appear in DTA measurements depend on specific area and on the heating rate. Experiments were done on yttrium aluminosilicate, samarium aluminosilicate and soda-lime silica glasses, slabs and powders. We found that some of them exhibit a dehydroxilation endothermic peak that overlaps at different extent with the crystallization peak. The dehydroxilation peak is not detectedwhen yttriumaluminosilicate glass powder is preheated at melting temperatures, or its surface is previously hydrated. For the yttrium aluminosilicate glass a dehydroxilation apparent activation energy of 255 ± 50 kcal mol−1 was obtained using the Kissinger plot.